STRENGTHENING CADRES CAPABILITIES IN THE DEVELOPMENT OF TODDLERS HEALTHY SNACK ON HIGH PROTEIN LOCAL MIXED FLOUR PRODUCTS IN ACCELERATION OF STUNTING MANAGEMENT IN TULUNGAGUNG - Annis Catur Adi; Fathrizqita Aghnia Raudhany; Wizara Salisa; Fariani Syahrul; Mahmud Aditya Rifqi (Jurnal Layanan Masyarakat (Journal of Public Services), 2022)
ABSTRACTStunting in Tulungagung Regency is still a serious threat to the health of infants and toddlers. The Covid-19 pandemic has hampered posyandu activities as health service facilities in the community. Strengthening the knowledge and skills of posyandu cadres is very important, because posyandu cadres are educational agents who are directly related to mothers of toddlers. This community service aims to increase the role of posyandu cadres in an effort to reduce stunting through the development of healthy snack innovations from high-protein flour products. There were three methods, namely counseling, training and mentoring. Counseling on stunting and the use of local food, training on making healthy snacks based on high-protein mixed flour, as well as mentoring participants in the development and innovation of healthy snacks based on high-protein mixed flour. The community service program was carried out in a hybrid manner, namely online and offline in the work area of the Pakel Health Center, with a total of 50 participants. The counseling was carried out using visual power point media, training with demonstrations of making healthy snacks, and mentoring which contained direct practice of making healthy snacks independently for two weeks after the counseling and training activities were carried out. The result shows that community service in the form of counseling has an impact on increasing the knowledge of Posyandu cadres at Pakel Health Center, by 4,5%. Training and assistance in making healthy snacks can also be practiced independently by cadres and mothers of toddlers as evidenced by the success and emergence of various menus. In conclusion, the counseling, training, and assistance provided were able to increase the creativity of posyandu cadres and mothers of toddlers in creating healthy snacks based on high-protein mixed flour as an acceleration of stunting prevention.